Religious Digital Literacy of Students in Indonesia and Malaysia - Muhammad Khakim Ashari; Moh Faizin; Jamaluddin Shiddiq (TADRIS: Jurnal Pendidikan Islam, 2023)
Advances in information and communication technology are so fast, capable of dynamically changing the order of human life. Everyone is increasingly dependent on technology in every inch of their activities, including in the realm of education. The use of technology products in the form of internet access and social media has been massively used by millions of people in the world. Learning, which initially only focused on meeting in class and relying only on printed books, is now developing with the presence of a new era, namely digital literacy, including in religious learning. This study aims to photograph the implementation of digital literacy, the use of digital religious resources and their impact on learning in Indonesia and Malaysia. This study is a type of qualitative research with a systematic literature review (SLR) approach. Primary data sources come from research journal articles and books that are in accordance with the theme of the discussion while secondary data is used as explanatory data related to the theme. The data analysis technique uses content analysis. The findings or results of the research are that digital literacy in Indonesia and Malaysia both utilize information and communication technology media that relies on internet access, websites and social media. Problems are still found in the two countries, namely related to equity, where in some regions or regions they have not been able to reach the internet optimally and certainly have not been able to fully implement digital literacy. Digital religious literacy of students in Indonesia and Malaysia is by utilizing interesting and free-access content and materials available on the internet and social media. Access to religious material in digital space by students has proven to be able to increase understanding of the material.